Application of cocoa pod husk (Theobroma cocoa Spp) for natural dyes powder on silk batik cloth. Issue 1 (December 2020) - Masiswo; Haerudin, A; Isnaini; Lestari, D W; Mandegani, G B; Satria, Y; Arta, T K; Atika, V
Abstract: The chocolate industry ( Theobroma cocoa ) in Indonesia reaches a total production of approximately 500 thousand tons. It has the potential to be used as natural dyes for the batik industry. This study aims to utilize cocoa pod husk powder on silk batik. The method was carried out by varying the concentration of maltodextrin as filler powder by 5%, 10%, and 15%, the final mordant variations (alum, calcium oxide, and ferrous sulfate) on silk cloth, and the natural dye solution of cocoa pod husk. The natural dye solution for cocoa pod skin was tested for phytochemistry to see the tannin and flavonoid content, the results of dyeing application on silk batik cloth were tested for the quality of its color resistance to washing, color strength, and color differences. The colorfastness test result showed a good category with an average value of 4-5 and the result of the color strength test showed that the best maltodextrin was 5% with a natural dye concentration of 15g / L. The results of alum mordant, calcium oxide, and ferrous sulfate (tunjung) produced colors that led to light and dark with a predominance of brown, red, and blackish brown.